Computer Simulation of Multi-Color Brainbow Staining and Clonal Evolution of B Cells in Germinal Centers - Meyer-Hermann, Michael; Binder, Sebastian C.; Mesin, Luka; Victora, Gabriel D. (Frontiers in Immunology, 2018)
Clonal evolution of B cells in germinal centres (GCs) is central to affinity maturation of antibodies in response to pathogens. Permanent or tamoxifen-induced multi-colour recombination of B cells based on the brainbow allele allows monitoring the degree of colour dominance in the course of the GC reaction. Here, we use computer simulations of GC reactions in order to replicate the evolution of colour dominance in silico and to define rules for the interpretation of these data in terms of clonal dominance. We find that a large diversity of clonal dominance is generated in simulated GCs in agreement with experimental results. In the extremes, a GC can be dominated by a single clone or can harbor many co-existing clones. These properties can be directly derived from the measurement of colour dominance when all B cells are stained before the GC onset. Upon tamoxifen-induced staining, the correlation between clonal structure and colour dominance depends on the timing and duration of the staining procedure as well as on the total number of stained B cells. %The time point of tamoxifen-induced staining is critical: Too early %reduces the number of lineages, too late reduces the correlation because %of staining ambiguities. B cells can be stained with 4 colours if a single brainbow allele is used, using both alleles leads to 10 different colours. The advantage of staining with 10 instead of 4 colours becomes relevant only when the 10 colours are attributed with rather similar probability. Otherwise, 4 colours exhibit a comparable predictive power. These results can serve as a guideline for future experiments based on multi-colour staining of evolving systems.